Non-linear modal interactions during rub-impact of a rotating flexible shaft. (April 2023) - Amaroju, Kartheek; Vijayan, Kiran; Friswell, Michael I
An understating on interaction between a rotating flexible member and a stationary element has a wide range of industrial applications. The focus of this study was to understand the modal interactions using a conceptual model. The conceptual model of the system consists of multiple disc rotors with a localised conduit. A theoretical model of the system was developed using finite element analysis. An eigenvalue analysis was carried out on the system and a Campbell diagram of the system was developed. The Campbell diagram provided information about the rotor speed wherein synchronization with the whirling modes occur. Further, a reduced order non-linear contact model was developed. A numerical bifurcation analysis with rotor speed as parameter was carried out on the reduced model. Analysis was carried out using randomized initial condition for each rotation speed. During the bifurcation study, certain rotation speed produced a high whirling response at speeds different from the critical speed. The increase in the response was associated with the internal resonance of whirling modes and rotor speed. The participating modes were identified using the Campbell diagram and full spectrum. The results from the theoretical model were validated using an experimental test rig. The identification of these internal resonance rotor speed can be useful in identifying the rotor speed exclusion zone and thereby improves the rotor life.